Technical Writing as Part of Project Management for Engineers: Using a Writing-Process Approach to Teach Disciplinary Writing Requirements - Wiederkehr, Ruth; Rudolf von Rohr, Marie-Thérèse (Journal of Academic Writing, 2020)
This article focuses on how formative feedback can be used to help engineering students write precise and coherent management summaries that appeal to a mixed audience. Management summaries are especially challenging to master as students must strive for a balance between adhering to scientific standards and being intelligible for a wider non-expert readership. Students of Energy and Environmental Technology at the school of engineering (FHNW) in Switzerland write a total of six technical reports about their project work (mostly in German). By analysing two management summaries, the focus is laid on the lecturers’ approach of relying on formative feedback which supports and accompanies the students’ iterative writing processes. It is shown how in early semesters lecturers provide hands-on guidance, such as suggesting discourse markers or pinpointing vague references to sharpen students’ awareness of the need to write as concisely as possible for mixed audiences.